RANCANG BANGUN ALAT PENDETEKSI SUARA, GETARAN DAN IMAGE TANK MENGGUNAKAN ARTIFICIAL NEURAL NETWORK - Iswono H. R.; Eko Kuncoro; Imam Ashar (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2021)
In this study, the created tool uses a camera to capture images of the tanks that will be detected and uses sound and vibration sensors to collect data on vibrations and sounds caused by objects, which will later be displayed in the visualization application. Based on the description that has been explained about the benefits of using radar and research related to the implementation of radar that can be developed in the military world, namely the development of sound, vibration and image detection equipment using artificial neural networks.